Physico-chemical, thermal and rheological characteristics of starch isolated from four commercial potatoes cultivars - Sanchez-González, J.A. (2019)
The physical-chemical, thermal and rheological properties of starches isolated from four commercial potato cultivars (Colparina, Huayro, Canchan and Yungay) were evaluated and characterized. The starches presented ovoid and spherical shapes, with average size from 20.08 ± 2.48 to 25.33 ± 6.54 μm and B-type granules, with amylose content from 15.49 ± 2.02 to 32.10 ± 0.14% and relative crystallinity, between 34.6 and 37.3%. The rheological properties measured using a dynamic rheometer, showed predominance storage module (G’) on the loss module (G’’) during the frequency range (0.01 - 3.20 Hz) studied, which would classify them as weak gels. The starches presented low syneresis, high clarity, pasting temperature from 65.70 ± 0.31 °C to 67.70 ± 0.23 °C, gelatinization start temperature (To); peak temperature (Tp); gelatinization final temperature (Tf) and gelatinization enthalpy (ΔH) values between 57.90 ± 0.24 and 62.23 ± 0.17 °C; 61.18 ± 0.01 and 64.85 ± 0.01 °C; 65.5 ± 0.31 and 68.34 ± 0.29 °C; 11.49 ± 0.8 and 15.43 ± 0.51 J/g, respectively. The starches evaluated had suitable properties to be used as ingredients in specific foods to improve their textural characteristics.